'I'm a different kind of biracial': how black/white biracial Americans with immigrant parents negotiate race. (3rd September 2017) - Waring, Chandra D. L.; Purkayastha, Bandana
ABSTRACT: Increasingly, multiracial families have garnered scholarly attention. However, the roles of ethnicity and immigrant ties are largely absent in bi/multiracial studies. Drawing on 17 in-depth interviews with black/white biracial Americans with at least one immigrant parent, this study analyzes the dynamic interplay of race, ethnicity, and immigrant roots in the bi/multiracial community. Our findings show that participants struggle to articulate the meaning of race, and they assert specific racial/ethnic identities to circumvent stereotypical connotations of whiteness and blackness. We highlight how biracial Americans with immigrant ties – those who we might assume would have a limited understanding of race – voice clear understandings of racial superiority and inferiority, racial relations, and racial stereotypes. Emphasizing their ethnic roots is not only an attempt to accurately describe their ancestry; it also allows them to avoid the social consequences (i.e. stereotypes, discrimination, etc.) of being (half) white or (half) black.